Type IV collagen reduces MUC5AC secretion in the lungs of ovalbumin-sensitized mice - Iwashita, Jun; Maeda, Hikari; Ishimura, Momo; Murata, Jun (Frontiers in Pharmacology, 2022)
Mucin 5AC (MUC5AC) is excessively secreted in the respiratory tract of patients with asthma. Suppressing this secretion is important for improving the air passages, which facilitates easy breathing. We have previously reported that the addition of type IV collagen, a typical extracellular matrix (ECM) protein, to the culture medium for human cell lines and primary cells reduced MUC5AC secretion. In this report, we further investigated the effect of type IV collagen on MUC5AC secretion in vivo. We employed ovalbumin (OVA)-sensitized mice to model of asthma and exposed them to type IV collagen to verify the reducing effect of MUC5AC in vivo. The amount of MUC5AC in bronchoalveolar lavage fluid was examined after nebulization of type IV collagen. Hypersecretion of MUC5AC of the OVA-sensitized mice was suppressed by type IV collagen exposure in a time- and dose-dependent manner. Furthermore, type IV collagen exposure to OVA-sensitized mice decreased integrin α2 and β1 expression in the lungs and increased the levels of Akt and extracellular signal-regulated kinase (ERK) phosphorylation in the trachea. These results suggest that type IV collagen suppresses MUC5AC hypersecretion via modulating integrin expression and Akt/ERK phosphorylation in the respiratory tract of the OVA-sensitized mice.